Malaysia : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
Malaysia's economy is showing signs of a gradual yet steady recovery thanks to the authorities' impressive vaccine rollout, swift and coordinated implementation of multi-pronged support measures. The recovery nevertheless remains uneven and the output gap sizeable, with significant downside risks. Going forward, the authorities should calibrate macroeconomic policies to the pace of the recovery, while preserving policy space given pandemic-related uncertainties, and simultaneously accelerate structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy